A case of bilateral coronoid hyperplasia in a child - YOSHITAKE, Hiroyuki; TAKAHARA, Namiaki; TAGUCHI, Nozomu; SATO, Fumiaki; YODA, Tetsuya; WAKE, So; YAMAGUCHI, Yoshihiro (Journal of the Japanese Society for the Temporomandibular Joint, 2020)
Objective: Hyperplasia of the coronoid process leads to restriction of mouth-opening consequent to contact of the coronoid process with the posterior surface of the body of the zygomatic bone and medial surface of the zygomatic arch. This paper describes a case of bilateral coronoid hyperplasia treated by bilateral coronoidectomies and the difficulty of postoperative management including mouth-opening exercises in a child.Patient: An eight-year old girl consulted our department with a complaint of restricted mouth-opening. Maximum mouth-opening (MMO) was 15 mm. Computer tomography (CT) showed bilateral hyperplasia of the coronoid process which extended above the zygomatic arch. We diagnosed bilateral coronoid process hyperplasia and performed bilateral coronoidectomies under general anesthesia. The coronoidectomies were carried out through an intraoral incision, which is similar to the incision of the surgical approach for sagittal split osteotomy. After releasing the temporalis muscles, coronoidectomies were performed with an ultrasonic cutting instrument.Mouth-closing exercises were begun on the first postoperative day. On the sixth postoperative day, mouth-opening exercises using her fingers were begun. On the eighth postoperative day, passive exercises including mouth-opening and protrusion were begun using the Yasec mouth-opening exercise device. One year after the surgery, MMO remains at 37 mm. Histopathological examinations showed normal bone tissue without any other lesions. It is suggested that neonatal or postnatal bilateral coronoid process hyperplasia may lead to the restriction of mouth-opening.Conclusion: We report a case of bilateral coronoid hyperplasia in a child. Trismus secondary to coronoid hyperplasia in a child is rare. Long-term follow-up is needed to observe the clinical outcome.